2018
DOI: 10.1038/s41396-018-0178-x
|View full text |Cite
|
Sign up to set email alerts
|

Eavesdropping and crosstalk between secreted quorum sensing peptide signals that regulate bacteriocin production in Streptococcus pneumoniae

Abstract: Quorum sensing (QS), where bacteria secrete and respond to chemical signals to coordinate population-wide behaviors, has revealed that bacteria are highly social. Here, we investigate how diversity in QS signals and receptors can modify social interactions controlled by the QS system regulating bacteriocin secretion in Streptococcus pneumoniae, encoded by the blp operon (bacteriocin-like peptide). Analysis of 4 096 pneumococcal genomes detected nine blp QS signals (BlpC) and five QS receptor groups (BlpH). Imp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 53 publications
(88 reference statements)
0
18
0
1
Order By: Relevance
“…Some bacteria, including L. gasseri EV1461, can "eavesdrop" on the quorum-sensing signals of competing species and respond by expressing broad-spectrum antibiotics, as well as by generating antimicrobial resistance strategies (42,89,92,93). Notably, the blp quorum-sensing system that regulates bacteriocin production in S. pneumoniae is highly polymorphic, and instances of cross-talk and eavesdropping between strains are common (9). Simulations using four strains with varying ability to sense neighbor's quorum-sensing signals show that eavesdropping can confer a fitness advantage with a negative frequency dependence (a strain present at low frequency can induce bacteriocin production to invade a more abundant population).…”
Section: Regulation Of Antagonismmentioning
confidence: 99%
See 1 more Smart Citation
“…Some bacteria, including L. gasseri EV1461, can "eavesdrop" on the quorum-sensing signals of competing species and respond by expressing broad-spectrum antibiotics, as well as by generating antimicrobial resistance strategies (42,89,92,93). Notably, the blp quorum-sensing system that regulates bacteriocin production in S. pneumoniae is highly polymorphic, and instances of cross-talk and eavesdropping between strains are common (9). Simulations using four strains with varying ability to sense neighbor's quorum-sensing signals show that eavesdropping can confer a fitness advantage with a negative frequency dependence (a strain present at low frequency can induce bacteriocin production to invade a more abundant population).…”
Section: Regulation Of Antagonismmentioning
confidence: 99%
“…Many toxins only target strains of the same species and therefore may not affect other competitors in the community. Further, the synthesis and secretion of these toxins may be physiologically costly and thus affect fitness (8,9). Toxins whose release requires cell lysis can only be deployed by a fraction of the population and will have different relative fitness costs and dynamics compared with actively secreted toxins.…”
mentioning
confidence: 99%
“…Cell to cell communication is an essential component of bacterial communities in order to modulate gene expression to best ensure survival. Although quorum sensing (QS) and interspecies communication can be used cooperatively in microbial communities, this pathway can also be exploited, allowing species to "eavesdrop" on neighboring species (Miller et al, 2018). QS can be blocked by inhibiting the production of signal, delivery of the signal, or detection of the signal.…”
Section: Communication Disruptionmentioning
confidence: 99%
“…Signaling associated with AI-2 in these bacteria is associated with adaptation to environmental conditions, affecting biofilm formation (Rickard et al, 2006; Lebeer et al, 2007; Cuadra-Saenz et al, 2012; Sun et al, 2014; Liu et al, 2017, 2018a) and resistance to stressors during the passage through the digestive tract (Yeo et al, 2015; Liu et al, 2018a). Additionally, the luxS system is required for the synthesis of bacteriocins by Escherichia coli (Lu et al, 2017), Streptococcus pneumoniae (Miller et al, 2018), Streptococcus mutans (Merritt et al, 2005; Sztajer et al, 2008), and Lactobacillus (Jia et al, 2017; Li et al, 2019). It was observed that AI-2 produced by Aggregatibacter actinomycetemcomitans is a factor directly involved in the inhibition of both biofilm formation and transformation into the filamentous form by Candida albicans (Bachtiar et al, 2014).…”
Section: The First Objection – the Selectivity Of Quorum Quenching Sumentioning
confidence: 99%